2020
DOI: 10.15698/mic2020.02.706
|View full text |Cite
|
Sign up to set email alerts
|

Influence of delivery and feeding mode in oral fungi colonization – a systematic review

Abstract: Postnatal acquisition of microorganisms from maternal and environmental sources contributes to the child microbiome development. Several studies showed that the mode of delivery and breastfeeding may have impact on the oral bacterial colonization, however, the influence on oral fungal colonization is still unknown. We performed a systematic literature review on mother to child oral fungi transmission, namely regarding the association between the mode of delivery and breastfeeding in oral yeast colonization. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“… 104 106 Azevedo et al. 107 found that delivery mode might be associated with a higher carriage of oral fungi at a young age. Ward et al 108 highlighted that the mode of birth likely influence the fungal composition of the infant.…”
Section: Factors Affecting Mycobiome In Early Lifementioning
confidence: 99%
“… 104 106 Azevedo et al. 107 found that delivery mode might be associated with a higher carriage of oral fungi at a young age. Ward et al 108 highlighted that the mode of birth likely influence the fungal composition of the infant.…”
Section: Factors Affecting Mycobiome In Early Lifementioning
confidence: 99%
“…178,179 A recent systematic review on this topic concludes that vaginal delivery appears to promote oral yeast colonization in early life, and that there is no difference between breastfed and bottle-fed infants. 180 During the first year of life, the oral cavity of 15% of 100 Swedish infants was colonized by Candida and its colonization at the age of 6 months correlated negatively with the concentration of lactoferrin in breast milk. 181 Based on a traditional culture approach, C. albicans and Candida parapsilosis have been identified as the most prevalent Candida species in infants 114 and in older children.…”
Section: Beyond Bacteria-acquisition and Establishment Of Other Micmentioning
confidence: 99%
“…Infants delivered vaginally to mothers with vaginal colonization by Candida had a higher prevalence of oral Candida than infants delivered by Cesarian section or infants delivered vaginally to mothers without vaginal Candida colonization 178,179 . A recent systematic review on this topic concludes that vaginal delivery appears to promote oral yeast colonization in early life, and that there is no difference between breastfed and bottle‐fed infants 180 . During the first year of life, the oral cavity of 15% of 100 Swedish infants was colonized by Candida and its colonization at the age of 6 months correlated negatively with the concentration of lactoferrin in breast milk 181 …”
Section: Postnatal Periodmentioning
confidence: 99%
“…Health outcomes in offspring are suggested to vary depending on the mode by which they were delivered. Vaginal birth, breastfeeding, and early childhood exposure to various microbes are some of the ways reported to set a child 8 of 19 | ISHIMWE up for a more symbiotic and protective microbiome (Azevedo et al, 2020;Funkhouser & Bordenstein, 2013;Schei et al, 2017;Shao et al, 2019;Van Nimwegen et al, 2011). The effect of the maternal gut microbiome on the offspring persist longer than those from exposure to vaginal and skin microbiome (Ferretti et al, 2018).…”
Section: Implications On Offspring Healthmentioning
confidence: 99%
“…The role of other microbes such as viruses and fungi is much less understood even though they are well known to be pathobionts in various infectious and inflammatory diseases. With recent methodological advancements, emerging reports are broadening our understanding of the microbiome by recognizing the potential contribution of other microbes other than bacteria including the virome and mycobiome (Azevedo et al, 2020; Li, Li, et al, 2019; Maqsood et al, 2019; Scarpellini et al, 2015; Vemuri et al, 2020). For example, the gut virome is altered in hypertensive patients and differentiated between normotensive and hypertensive phenotypes better than gut bacteria (Han et al, 2018).…”
Section: Microbiome and Host Healthmentioning
confidence: 99%